Ajaran Abu Bakar Bappu - Awang Kechik, Ab. Aziz (Jurnal Usuluddin, 1996)
Abu Bakar Bappu according to Islamic Jurisprudence is one of the misleading teacher in Kluang, Johor. This article tries to elaborate comprehensively this topic according to his beliefs.